GAMBARAN KEPATUHAN AKSEPTOR KB SUNTIK SELAMA PANDEMI COVID-19 DI PUSKESMAS SIMPUR BANDAR LAMPUNG - Radimas Lingga Yuwaka (Universitas Pahlawan Tuanku Tambusai, 2022)
The baby boom during the Covid-19 pandemic in Indonesia will have a serious impact and need intensive and serious handling. This shows that there is a need to control population growth in Indonesia. One of the methods used by the BKKBN to support family planning programs is contraception. So the researchers wanted to know the compliance of injection family planning participants' visits during the pandemic. The purpose of this study was to determine the compliance of injection family planning visits during the Covid-19 pandemic and the frequency distribution of the factors of adherence to the compliance of injection family planning acceptor visits during the Covid-19 pandemic at the Simpur Health Center Bandar Lampung 2021. The research method used was descriptive with the method cross-sectional. The population in this study were all active injecting family planning acceptors in July, August, and September. Sampling technique with non-probability sampling method with purposive sampling technique. The research sample obtained was 78 respondents. By collecting data using a questionnaire sheet with a Likert scale. The results showed that from a sample of 78 respondents, the majority of respondents aged 20-30 years were 62 respondents (79.5%). The majority of respondents reached the last high school education as many as 47 respondents (60.3%). Based on the occupation of the majority of respondents as housewives, namely 31 respondents (39.7%). The majority of respondents had good knowledge reaching 58 respondents (74.4%), respondents who received good husband support reached 60 respondents (76.9%), the majority of respondents received good health services as many as 41 respondents (52.6%), for economic status, some 33 respondents (42.3%) have income <4,000,000, the majority of respondents have a good attitude as many as 42 respondents (53.8%), and as many as 60 respondents (76.9%) make appropriate return visits time or comply with repeat visits.